Massive urethrorrhagia due to a blunt perineum injury; a report of a case with bulbar pseudoaneurysm - Khorami, Mohammad Hatef (Urol Case Rep, 2021)
Blunt perineum trauma rarely leads to massive urethrorrhagia due to the formation of a bulbar aneurysm. A 29-year-old man with unstable hemodynamic underwent a digital subtraction angiography (DSA), which revealed a pseudoaneurysm in the penile bulb supplied from both internal pudendal arteries fistulized to the urethral duct bulb. A catheter was inserted into the distal part of pudendal arteries at the pseudoaneurysm's proximity, and an intermittent embolizing agent (Gel-foam) was injected. The pseudoaneurysm was filled with Gel-foam. Despite the superiority of conservative management, urethrorrhagia's life-threatening nature calls for angiographic intervention, successfully embolized using gel-foam with negligible complications.